Silap-silap tersilap makna! - Mohd Saad, Muhammad Luqman Ibnul Hakim; Tengku Abdul Aziz, Tengku Mohd Farid (Universiti Teknologi MARA, Kedah, 2025)
The Academy of Language Studies, Universiti Teknologi MARA (UiTM) Kedah branch is proud to present the first issue of its e-magazine, The Epitome, as our focus to highlight our commitment to contribute to the areas of creative writing. THE EPITOME aims to provide a platform for writers, educators, academicians, poet, and researchers to share their ideas, findings, knowledge, and experience, particularly on various creative writing genres - personal essays, poetry, short stories, songs, movie scripts, plays, and innovative projects in four different languages ( English, Bahasa Melayu, Mandarin, and Arabic).